2022
DOI: 10.3389/fpsyt.2022.779326
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function Mediates the Anti-suicide Effect of Repeated Intravenous Ketamine in Adult Patients With Suicidal Ideation

Abstract: ObjectivePrior research has shown that ketamine has anti-suicide effects. Additional evidence also suggests that ketamine may offer pro-cognitive effects. Herein, we propose that the anti-suicide effects of ketamine are partially mediated via pro-cognitive effects. We aimed to determine whether improvement in cognitive function mediated change in suicidal ideation was associated with ketamine treatment.MethodsUnipolar or bipolar depressive patients (n = 86) with suicidal ideation received six infusions of keta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Repeated infusion of ( R,S )-ketamine (0.5 mg/kg) caused significant improvement of working memory in MDD patients with PTSD [ 89 ]. Interestingly, depression symptom severity and processing speed performance in patients with MDD or BD partially mediated the improvements in suicidal ideation after repeated infusion of ( R,S )-ketamine [ 90 ]. A recent systematic review indicated potential procognitive effects of subanesthetic doses of ( R,S )-ketamine among patients with depression, although there is evidence for immediate altered cognitive dysfunction in healthy subjects [ 91 ].…”
Section: Introductionmentioning
confidence: 99%
“…Repeated infusion of ( R,S )-ketamine (0.5 mg/kg) caused significant improvement of working memory in MDD patients with PTSD [ 89 ]. Interestingly, depression symptom severity and processing speed performance in patients with MDD or BD partially mediated the improvements in suicidal ideation after repeated infusion of ( R,S )-ketamine [ 90 ]. A recent systematic review indicated potential procognitive effects of subanesthetic doses of ( R,S )-ketamine among patients with depression, although there is evidence for immediate altered cognitive dysfunction in healthy subjects [ 91 ].…”
Section: Introductionmentioning
confidence: 99%
“…Novak et al reported that higher baseline cognitive flexibility was associated with lower suicidal ideation 3 months after psychiatric discharge among patients treated with oral antidepressants (Novak et al, 2022). Over the nearly 10 years that low-dose ketamine infusion has been believed to rapidly exert an antisuicidal effect, evidence suggested the predictive role of baseline cognitive function on this antisuicidal effect (Chen et al, 2021; Lee et al, 2016; Price et al, 2014; Zhou et al, 2022). Price et al performed the implicit-association test (ITA) to assess the relative speed with which patients classified words when a given manual key response was required for two constructs (escape/stay and me/not me), and they discovered that higher implicit “Escape = Me” ITA scores were associated with less severe suicidal symptoms among patients who underwent ketamine infusion (Price et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Price et al performed the implicit-association test (ITA) to assess the relative speed with which patients classified words when a given manual key response was required for two constructs (escape/stay and me/ not me), and they discovered that higher implicit "Escape = Me" ITA scores were associated with less severe suicidal symptoms among patients who underwent ketamine infusion (Price et al, 2014). Zhou et al reported that processing speed and verbal learning, but not working memory, significantly improved after six ketamine infusions in patients with MDSI; they also identified an association between higher pretreatment processing speed and less postinfusion suicidal ideation (Zhou et al, 2022). In this study, we discovered that both working memory and response inhibition (go/no-go task) at baseline were associated with the remission of suicidal symptoms after ketamine infusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations